2018
DOI: 10.5194/acp-2018-687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of the main primary source profiles of particulate matter across China: from 1987 to 2017

Abstract: <p><strong>Abstract.</strong> Based on the published literatures and typical profiles from the source library of Nankai University, a total of 3244 chemical profiles of the main primary sources of ambient particulate matter across China from 1987 to 2017, including coal combustion, industrial emissions, vehicle emissions, fugitive dust, biomass burning, and cooking emissions, were investigated and reviewed to trace the evolution of their main components and identify th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Industrial emissions and biomass burning are two important sources of atmospheric pollutants over eastern China (Bi et al., 2019; Wang et al., 2005) and are likely to emit abundant MSA precursors as mentioned above. Unfortunately, there is little information about the emission factor for volatile organic sulfur compounds from these sources.…”
Section: Resultsmentioning
confidence: 99%
“…Industrial emissions and biomass burning are two important sources of atmospheric pollutants over eastern China (Bi et al., 2019; Wang et al., 2005) and are likely to emit abundant MSA precursors as mentioned above. Unfortunately, there is little information about the emission factor for volatile organic sulfur compounds from these sources.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study using the GEOS-Chem-TOMAS model identified significant aerosol emissions from biomass burning in India and Indonesia from residential, agricultural, and wildfire sources (Kodros et al, 2018). Direct burning has been reported to be a common technique to eliminate agricultural residuals in both China and India (Bi et al, 2019). The contribution of biomass burning to urban aerosols was confirmed by the high content of water-soluble potassium in the particle-phase (Qi et al, 2015;Zheng et al, 2005).…”
Section: Sub-micron Urban Aerosol Number Psds In Asia: Factors Contrimentioning
confidence: 99%